2009
DOI: 10.1002/prep.200700220
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Advanced RDX/TATB Based Low Vulnerable Sheet Explosives with HTPB Binder

Abstract: Hydroxyl‐terminated polybutadiene (HTPB) based sheet explosives incorporating insensitive 1,3,5‐triamino‐2,4,6‐trinitrobenzene (TATB) as a part replacement of cyclotrimethylene trinitramine (RDX) have been prepared during this work. The effect of incorporation of TATB on physical, thermal, and sensitivity behavior as well as initiation by small and high caliber shaped charges has been determined. Composition containing 85% dioctyl phthalate (DOP) coated RDX and 15% HTPB binder was taken as control. The incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…HTPB is a preferred choice due to its clean curing reactions, stable urethane linkages formed by isocyanate curing, and superior fuel content. The application of HTPB can be extended to sheet explosives [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTPB is a preferred choice due to its clean curing reactions, stable urethane linkages formed by isocyanate curing, and superior fuel content. The application of HTPB can be extended to sheet explosives [7].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above and our continued research and development work in the area of sheet explosives [3,4,7], we report here studies on the incorporation of CL-20 in sheet explosive formulations. The sensitivity, performance and thermolysis data obtained for the CL-20 based sheet explosive formulations are compared with RDX based sheet explosive under similar experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…HTPB based sheet explosive formulations have also been reported 13,14 . Thermal characterisation and analysis of energetic materials and their formulations are important not only for understanding the kinetics of their thermal decomposition, but also for assessing the effect of their exothermic decomposition on the potential hazards in their handling, processing, and storage 15,16 .…”
mentioning
confidence: 99%
“…Thermal characterisation of PBX containing RDX or HMX with HTPB-binder has been reported by different authors [17][18][19][20][21] . The performance, sensitivity and thermal analysis data obtained from HMX-based sheet explosive formulation have been compared in this paper with the existing conventional RDX-based sheet explosive formulation 13,14 .…”
mentioning
confidence: 99%
“…Joseph et al [12] have reported hydroxyl terminated polybutadiene (HTPB) binder based sheet explosive compositions with an average VOD of 7200 m/s. A CL-20 based sheet explosive has also been reported with a VOD of 7680 m/s [13].…”
mentioning
confidence: 99%